Validity of Ligand Efficiency Metrics - Murray, Christopher W. (American Chemical Society, 2014)
A recent viewpoint article (Improving the plausibility of success with inefficient metrics. ACS Med. Chem. Lett.2014, 5, 2–5) argued that the standard definition of ligand efficiency (LE) is mathematically invalid. In this viewpoint, we address this criticism and show categorically that the definition of LE is mathematically valid. LE and other metrics such as lipophilic ligand efficiency (LLE) can be useful during the multiparameter optimization challenge faced by medicinal chemists.